2007
DOI: 10.1021/ja073576y
|View full text |Cite
|
Sign up to set email alerts
|

Vi -Value Analysis:  A Pressure-Based Method for Mapping the Folding Transition State Ensemble of Proteins

Abstract: Here we introduce an approach to mapping the folding transition state ensemble of proteins based on the pressure dependence of protein stability. Previously, we have shown that the activation volume for folding of wild type (WT) SNase is large and positive, and hence that the rate-limiting step in folding involves significant dehydration. In contrast, variants bearing buried ionizable residues at position 66 were shown recently to fold through a highly hydrated transition state ensemble (TSE). We present the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
87
0
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 37 publications
(94 citation statements)
references
References 27 publications
5
87
0
2
Order By: Relevance
“…Our results also indicate that the volume difference is dominated by changes in the polar and positively charged residues. These results are consistent with some of the findings of Mitra et al that, in general, at ambient temperatures a negative sign comes about by a positive contribution from nonpolar groups that is outweighed by a negative contribution from polar groups as well as the hydration of cavities (not explicitly investigated here, but accounted for) [55]. However, the use of a fully extended denatured state clouds this comparison.…”
Section: Resultssupporting
confidence: 92%
“…Our results also indicate that the volume difference is dominated by changes in the polar and positively charged residues. These results are consistent with some of the findings of Mitra et al that, in general, at ambient temperatures a negative sign comes about by a positive contribution from nonpolar groups that is outweighed by a negative contribution from polar groups as well as the hydration of cavities (not explicitly investigated here, but accounted for) [55]. However, the use of a fully extended denatured state clouds this comparison.…”
Section: Resultssupporting
confidence: 92%
“…We have shown that the conformations at the folding barrier for WT and Δ+PHS resemble the main intermediate, with a collapsed and solvent excluded central core and a disrupted C-terminal helix. 7 This TSE must also be destabilized in I92A, and thus I92A likely folds through multiple alternate pathways involving the intermediates detected here.…”
Section: Interpretation Of Apparent Volume Changes Formentioning
confidence: 78%
“…84 Recent explicit-water simulations of two-helix systems 78 has revealed an intimate relationship between the enthalpic contribution to the overall folding barrier and the activation volume of folding transition state determined from pressure-based experimental methods. 85 The The schematic molecular drawings illustrate the distances between the methane molecules (full circles) at the cm, db, and ssm positions vis-à-vis the size of a water molecule (dashed circles). For the example in this figure, the r cm distance, the db height ɛ db , and the ssm depth ɛ ssm in U(r) (continuous curve) are shown with values equal to those in the methane-methane PMF from atomic simulation (dashed curve).…”
Section: Theorymentioning
confidence: 99%
“…Thus, formation of the helix dimer entails surmounting an "activation volume" (peak of volume increase as the two helices approach each other from large separation) of ≈ 55 mL/mol and ≈ 150 mL/mol, respectively, for a pair of 20-residue polyalanine and polyleucine helices (Fig. 3 85), suggesting that the extent of dehydration at the folding rate-limiting step of this protein may be similar to that typified by the dimerization of two rigid 20-residue polyalanine helices. This comparison between activation volume data from pressure experiments and from explicit-water simulation of many-body hydrophobic interactions provided further support to the hypothesis that the ratelimiting step of folding for some proteins likely involves large-scale, near-simultaneous hydrophobic burial.…”
Section: Theorymentioning
confidence: 99%